Design and Implementation of House Rental Management System Based on SSM Framework - Xu, Dequan; Peng, Shuangyun; Du, Yuanyuan (IEEE Advanced Information Management, Communicates, Electronic and Automation Control Conference (IMCEC ...) (Online), 2022)
Today's widespread use of the Internet has brought a lot of convenience to life. Therefore, by integrating the housing lease management with the closely related network in life, and using mature JSP technology to develop and implement the housing lease management system, the diversification and informatization of the housing lease management system can play a significant role in further improving the development of the leasing industry and enriching the housing lease management experience. The system chooses a feasible development scheme according to the actual situation, and realizes all the functions of the system with the help of JSP, SSM framework, MySQL database and other cutting-edge technologies. Next, it tests the system, including whether the system has loopholes, whether the user permission functions are abnormal, and so on, so as to improve the system and finally make the system meet the relevant development standards.